Assessment of a prognostic biochemical indicator of nutrition and inflammation for identification of pressure ulcer risk. Issue 3 (27th February 2006) - Reynolds, T M; Stokes, A; Russell, L
Abstract : Background: Pressure ulcers represent a major cost to the healthcare systems of the world but preventative measures are expensive and could be better targeted. Current risk screening mechanisms are often subjective and could be improved. Aims: To evaluate whether a biochemical assessment tool (Prognostic Inflammatory and Nutritional Index; PINI) based on measurement of albumin, α1-acid glycoprotein, C-reactive protein, and prealbumin is of value in estimating the prognosis of patients with pressure ulcers of European Pressure Ulcer Advisory Panel grade 1 and above. Methods: Serum samples were collected from patients participating in a clinical trial of a pressure ulcer preventing mattress. These were analysed for the markers listed above and the PINI calculated. PINI was then evaluated against patient outcome. Results: A statistically significant difference between PINI values in patients whose pressure ulcers improved and those whose ulcers worsened was found in parametric testing, but significance was not achieved in non-parametric testing. A receiver operating characteristic plot showed the PINI was superior to chance in estimating prognosis. Conclusions: The PINI appears to offer a potential route to improving pressure ulcer risk estimation and thus allocation of scarce equipment to improve prevention.